2009
DOI: 10.1017/s0066477400001994
|View full text |Cite
|
Sign up to set email alerts
|

Catullus and the Brothel-Creepers:Carmen37

Abstract: Salax taberna vosque contubernales,a pilleatis nona fratribus pila,solis putatis esse mentulas vobis,solis licere, quidquid est puellarum,confutuere et putare ceteros hircos? 5an, continenter quod sedetis insulsicentum an ducenti, non putatis ausurumme una ducentos irrumare sessores?atqui putate: namque totius vobisfrontem tabernae sopionibus scribam. 10puella nam mi, quae meo sinu fugit,amata tantum quantum amabitur nulla,pro qua mihi sunt magna bella pugnata,consedit istic. hanc boni beatiqueomnes amatis, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Watson (2009) has shown that Catullus uses the characteristic language of Roman prostitution throughout the poem to present the salax taberna as a brothel as well as a bar, and this representation also fits aspects of the Epicurean tradition. The time Epicurus spent with hetairai, and his admission of women to his philosophical school, was a constant element in hostile accounts of his life 30 .…”
Section: Catullus 37: the Epicurean Herdmentioning
confidence: 99%
“…Watson (2009) has shown that Catullus uses the characteristic language of Roman prostitution throughout the poem to present the salax taberna as a brothel as well as a bar, and this representation also fits aspects of the Epicurean tradition. The time Epicurus spent with hetairai, and his admission of women to his philosophical school, was a constant element in hostile accounts of his life 30 .…”
Section: Catullus 37: the Epicurean Herdmentioning
confidence: 99%